Alcidodes karelinii (Coleoptera: Curculionoidea: Molytinae): New weevil species for the fauna of Serbia - Vukajlović Filip N.; Ugrnov Danilo; Rapajić Branko; Ćoćić Danijela; Banjanac Sanja; Tot Ivan (Kragujevac Journal of Science)
This paper reports the first findings of the allochthonous weevil species Alcidodes karelinii (Boheman, 1844) in Serbia. It is distributed throughout the Eurasian steppe belt, and recently it has been spreading westwardly. The specimens from Serbia were found thanks to citizen science in two localities in Vojvodina Province (North Serbia): Ada Municipality, North Banat District, December 16th , 2022, and March 16th , 2024; and the Village of Bački Brestovac, Odžaci Municipality, West Bačka District, September 25th, 2023.